Treatment of Casualties in a Forward Hospital of Indian Army : Nine year Experience - Rai, KM (Med J Armed Forces India, 2004)
BACKGROUND: To analyze the outcome of the management of casualties in a level II trauma centre of a forward hospital of Armed Forces over a nine year period. Retrospective analysis of all casualties received in a single forward hospital of Indian Army was carried out. METHOD: During 9 years (1990-1998), a total of 5737 casualties were received in a single level II zonal hospital of the Army in a forward area. Majority of the injuries were caused by bullets, or by fragments of improvised explosive devices. A policy of aggressive resuscitation and early primary repair of injuries was followed. General surgeons routinely performed craniotomies, thoracotomies, laparotomies, stabilization of fractures by fixators and repair of vascular injuries. RESULT: 38% of patients had injuries to several body parts (polytrauma), resulting in a total of 8578 injuries. Region-wise distribution of injuries was as follows : 14.2% head and neck injuries, 13.3% chest wounds, 13.5% abdominal injury and 59% extremity wounds. The overall mortality rate was 3.6%. The complication rate was about 7% with infection as the major complication. The results of primary repair of colonic injuries were similar to those of staged repairs. The results after primary closure of war wounds were better than those treated with delayed primary closure in selected cases. CONCLUSION: Prompt evacuation, speedy resuscitation and early definitive repair of war injuries results in low mortality and morbidity. A motivated and dedicated team and adequate availability of blood and ancillary services adds to the excellent outcome. The policy of primary repair of colonic and selected soft tissue injuries appears justified in selected cases.